2019
DOI: 10.1136/bcr-2019-232326
|View full text |Cite
|
Sign up to set email alerts
|

Organising pneumonia in Rhupus syndrome

Abstract: Interstitial lung disease (ILD) is seen in 17% of patients with Rhupus syndrome. Organising pneumonia (OP), a subtype of connective tissue disease-associated ILD, is rare but associated with good outcomes. Here, we present a patient with Rhupus who developed OP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[10,14,15] (Table 3). In the same systematic review, 202 of 287 patients were identified with hematological abnormalities, but only a few instances showed autoimmune hemolytic anemia, the majority of which had favorable outcomes [10,[16][17][18][19][20][21][22] (Table 3). Our patient was diagnosed with an overlap between RA and SLE based on clinical signs and symptoms and serological findings, and her illness was complicated by lupus nephritis, autoimmune hemolytic anemia, and CNS vasculitis, which improved following administration of steroids, hydroxyquinone, and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…[10,14,15] (Table 3). In the same systematic review, 202 of 287 patients were identified with hematological abnormalities, but only a few instances showed autoimmune hemolytic anemia, the majority of which had favorable outcomes [10,[16][17][18][19][20][21][22] (Table 3). Our patient was diagnosed with an overlap between RA and SLE based on clinical signs and symptoms and serological findings, and her illness was complicated by lupus nephritis, autoimmune hemolytic anemia, and CNS vasculitis, which improved following administration of steroids, hydroxyquinone, and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…On HRCT, OP shows ground glass opacities, consolidations and peribronchovascular opacities. OP has also been described in rhupus syndrome [ 61 ]. CS are the treatment of choice.…”
Section: Parenchymal Lung Diseasementioning
confidence: 99%
“…Several immunosuppressant agents, such as azathioprine, MMF, cyclosporin, CYC and plasmapheresis, have been used in various case reports. [ 58 , 59 , 60 , 61 , 62 ]. Finally, an association between SLE and pulmonary sarcoidosis has been described [ 10 , 63 , 64 , 65 , 66 ].…”
Section: Parenchymal Lung Diseasementioning
confidence: 99%